THE ANALYSIS OF PROBLEM BASED LEARNING (PBL) IN MICRO TEACHING COURSE TO FIT THE REQUIREMENT OF EFFECTIVE PRE-SERVICE TEACHERS - Linda, Linda; -, Apandi (Universitas Swadaya Gunung Jati, 2019)
One of phenomena that occur in the educational world is the issue of discrepancies that occur between theory the pre-service teacher learned in college with implementation when they should teach in thereal fields (schools). Problem Based Learning (PBL) becomes one of the efforts to bridge the existing problems. This research is conducted to find out the extend of Problem Based Learning (PBL) in Micro Teaching course since the course must be accomplished by students before carrying out practical activities in the real field in the school at teaching training program. The writer uses descriptive qualitative method. And in this research the writer uses case study as a research design to find out the purpose of the research. The participants of the the research are 8 students from a class of micro teaching course in English Department of Universitas Swadaya Gunung Jati. In this paper, The Students as the Pre Service Teacher(s) are coded PST(s). The writer uses observation as the instruments of the research. Theory of Miles and Huberman are used to collect data from observation. Regarding to the discussion above, the four aspects of competences of effective teacher are shown in the teaching practice done by the students of Micro teaching course that apply Problem Based Learning (PBL). The majority results of the observation explain that applying Problem Based Learning in Micro Teaching course develops pre-service teachers competence in their teaching in classroom. This research shows pre-service teachers can integrate their competences and create good performance in their teaching practice.